K+ Channels: Function-Structural Overview - Rojas-Montecinos, P (2012)
Potassium channels are particularly important in determining the shape and duration of the action potential, controlling the membrane potential, modulating hormone secretion, epithelial function and, in the case of those K+ channels activated by Ca2+, damping excitatory signals. The multiplicity of roles played by K+ channels is only possible to their mammoth diversity that includes at present 70 K+ channels encoding genes in mammals. Today, thanks to the use of cloning, mutagenesis, and the more recent structural studies using x-ray crystallography, we are in a unique position to understand the origins of the enormous diversity of this superfamily of ion channels, the roles they play in different cell types, and the relations that exist between structure and function. With the exception of two-pore K+ channels that are dimers, voltage-dependent K+ channels are tetrameric assemblies and share an extremely well conserved pore region, in which the ion-selectivity filter resides. In the present overview, we discuss in the function, localization, and the relations between function and structure of the five different subfamilies of K+ channels: (a) inward rectifiers, Kir; (b) four transmembrane segments-2 pores, K2P; (c) voltage-gated, Kv; (d) the Slo family; and (e) Ca2+-activated SK family, SKCa. © 2012 American Physiological Society.